Utilization of Ginger to Increase Community Welfare in Singapadu Kaler Village - Putri Setianingsih Putri; Ni Made Ayu Suardani Singapurwa; Luh Suriati; Salensia Haryati Afons; A.A. Made Semariyani; I Gede Pasek Mangku; I Wayan Sudiarta; I Putu Candra; I Nyoman Rudianta (Asian Journal of Community Services, 2023)
Ginger is an untapped commodity in Singapadu Kaler Village. To empower rural communities through increasing knowledge, attitudes, skills, and behaviors, activities and mentoring programs are needed that are under the needs of the community. Processing of ginger into various products such as candied ginger and instant ginger has been produced and marketed by PKK women. PKK women do not yet have adequate entrepreneurial, production management, and marketing skills. The solution to overcome partner problems is to provide the right technology for processing candied ginger and instant ginger, equipment assistance, knowledge of product packaging and labeling, marketing, and entrepreneurship. Based on the evaluation results, this group mastered the technology of making candied ginger and instant ginger up to 75%.